2010
DOI: 10.1177/1553350610376393
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of Wound Healing and Oxidative Process by Montelukast in Experimental Colon Anastomoses

Abstract: ML causes impairment of wound healing without altering the anastomosis bursting pressure and reverses the oxidative damage of the colon anastomoses in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
(29 reference statements)
0
11
0
1
Order By: Relevance
“…Montelukast, one of the selective reversible CysLT 1 receptor antagonist, is used for the maintenance treatment of asthma and to relieve symptoms of seasonal allergies [34]. It is reported that montelukast can reduce eosinophilic inflammation in the airways [3537].…”
Section: Discussionmentioning
confidence: 99%
“…Montelukast, one of the selective reversible CysLT 1 receptor antagonist, is used for the maintenance treatment of asthma and to relieve symptoms of seasonal allergies [34]. It is reported that montelukast can reduce eosinophilic inflammation in the airways [3537].…”
Section: Discussionmentioning
confidence: 99%
“…33 It is reported that montelukast can reduce eosinophilic inflammation in the airways. [34][35][36] Besides, CysLT1 receptor antagonists or biosynthesis inhibitors ameliorate ethanol-induced gastric mucosal damage, 37,38 experimental colitis, 39 and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oral treatment of ML has effect on the maintenance treatment of asthma and relieve symptoms of seasonal allergies in adults and children 8 . Several studies also showed that ML has a significant antioxidative effect on inhibition of lipid peroxidation in some tissues such as testis and liver 9,10 .…”
Section: Montelukast (Ml) Is An Anti-inflammatory Drugmentioning
confidence: 99%